The Small-Scale Satellite Modular Hyperspectrometer - A. O. Martinov; Yu. V. Beliaev; B. I. Beliaev; A. V. Chumakov; A. V. Damaratski (Приборы и методы измерений, 2019)
Recently in the world practice of aerospace monitoring of the Earth there has been an increasingly active using of methods and devices of hyperspectral imaging. Thus creation of systems designed for recording hyperspectral data and methods for their processing is an actual task for remote sensing of the Earth. The aim of the article was to develop and create a small-sized satellite modular hyperspectrometer in visible and near infrared range, designed to receive information on remote sensing of the Earth in order to constantly update data about state of natural environment and infrastructure objects using videospectral methods with the possibility of comprehensive study of both spectral and spatial characteristics of the observed objects.A small-scale satellite modular hyperspectrometer has been developed. The distinctive features of the equipment include high spectral resolution and small dimensions. A hyperspectrometer includes two main modules: an optical module and an electronics one. The design feature of the optical module is the use of a concave holographic diffraction grating in a polychromator. The electronics module is based on a single board computer. Their description and design features, a scheme for the formation of a hypercube and software for its further processing are presented in the paper. The developed hardware (test equipment, a space experiment simulator and a spatial scanning system) for efficiency testing is presented also, as well as test measurements ware conducted. It is worth noting the extremely small dimensions for this class of devices in comparison with analogues as well as the vibration resistance of the equipment.